2013
DOI: 10.1002/pssb.201300068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact geometry on magnetoresistance in CoPd-contacted carbon nanotubes

Abstract: We present local magnetoresistance measurements on carbon nanotubes contacted with the ferromagnetic alloy Co50 Pd50. A sample with contacts of dimensions thickness=10nm, normallength=4thinmathspaceμm exhibited the typical sharp switching expected at the coercive fields of the contacts. However, a sample with the same in‐plane geometry but a thickness of 40 nm displayed a complicated switching behavior indicative of gradual domain wall rotation. In both samples, the contact widths were varied to control shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, since the injection of charge carriers occurs only at the point where the contact ends [25], the local magnetic environment has a strong influence on the MR measurements. Importantly, pinning and moving of domain walls in contacts that incorporate several magnetic domains leads to unstable switching behavior of the contacts and a non-trivial MR signal [26]. For this reason, we optimized the shape of the contacts in such a way that the magnetization is in-plane along the long axis with a single or at most two domains [22].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, since the injection of charge carriers occurs only at the point where the contact ends [25], the local magnetic environment has a strong influence on the MR measurements. Importantly, pinning and moving of domain walls in contacts that incorporate several magnetic domains leads to unstable switching behavior of the contacts and a non-trivial MR signal [26]. For this reason, we optimized the shape of the contacts in such a way that the magnetization is in-plane along the long axis with a single or at most two domains [22].…”
Section: Methodsmentioning
confidence: 99%
“…Following this publication, there have been some very interesting studies all from the Meyer's group in Jülich. [ 101–103 ] In particular, this team focused on the impact of the native tunnel barrier between CoPd contacts (PCoPd25%${P_{{\rm{CoPd}}}} \cong 25\% $) [ 101,102 ] and a (single and multiwall) carbon nanotube on the amplitude of the MR effects. They showed that the MR increases when the contacts are resistive (>100 kΩ) especially at low temperatures compared to simple ohmic contacts whose resistance does not vary much with temperature.…”
Section: Spin Transport Experiments In Carbon Nanotubesmentioning
confidence: 99%
“…The weak spin–orbit coupling and hyperfine interaction in a carbon nanotube (CNT) as well as the observation of long spin-flip scattering lengths of at least 130 nm in a multiwalled CNT and 1 μm in single-walled (SW) CNTs have prompted researchers to use these low dimensional materials as the spacer in next-generation MTJs. Despite the challenges in fabricating reliable magnetic contacts with CNTs, several groups have been successful in demonstrating a magnetoresistive effect in carbon nanotube based MTJs. , Measurements in two-terminal junctions reveal a considerable variation in magnetoresistance, , ,, which could be ascribed to the lack of chirality control in CNTs and difficulty in fabricating reproducible junctions. In the case of a three-terminal CNT-based MTJ, Sahoo et al first observed an electric field modulation of MR; an oscillation with a strong variation in the amplitude and width of the MR signal with gate bias was reported .…”
Section: Introductionmentioning
confidence: 99%